Method of solidifying a layer deposited on a substrate and substrate produced using the method
Patent Information
- Application Number
- CN202580010004.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-01-15
- Filing Date
- 2025-01-14
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]2. 根据天气条件,固化可能会停滞,导致未固化的内部和固化的顶表面,从而产生在涂层宽度上的性能差异
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention relates to a method for curing a layer comprising a coating formulation containing hydrolyzable Si-X groups. X is selected from halogens, C1-C6 alkoxy groups, hydrogen, -NH-Si, and -NH2, and the substrate comprising the coating prepared using this method. Background Technology
[0002] Compounds containing hydrolyzable Si-X groups are commonly used in coating formulations as a main component or additive. Curing of such coatings involves the hydrolysis of the Si-X groups to form silanols, followed by a condensation reaction between the silanol groups to form Si-O-Si bonds. Because they do not require or involve toxic curing agents or groups—whether as part of the molecule or as separate additives—they are considered environmentally friendly. Furthermore, Si-O-Si bonds are highly stable against UV and other environmental factors, as well as against a wide variety of chemicals.
[0003] The Si atoms in the Si-X group or other Si atoms in the molecule can also be bonded to organic groups such as methyl, ethyl, phenyl, or vinyl (CH=CH2). These highly inert organic Si groups impart good hydrophobicity and even oleophobicity to coatings. This is why such compounds are used as antifouling coatings or surface modifiers to impart antifouling properties. Examples of compounds containing hydrolyzable Si-X groups include (poly)alkoxysilanes, (poly)halosilanes, and (poly)silazanes.
[0004] Coatings containing hydrolyzable Si-X groups are typically cured in an ambient atmosphere, meaning their curing is driven by atmospheric moisture. This curing method is simple and environmentally friendly because it does not use toxic curing agents, such as tin-based compounds. However, this curing typically proceeds from the surface inwards, meaning the top surface of the coating cures before or faster than the interior. The result is: 1. Curing typically slows down over time because the cured top surface acts as a buffer against moisture penetration. This is especially true when Si atoms are bonded to organic groups such as the methyl and vinyl groups in polysilazanes. These Si-alkyl groups (e.g., Si-CH3) or Si-aryl (Si-phenyl) groups are hydrophobic and inert, and therefore prevent moisture from entering. In fact, in organic chemistry, their inertness and hydrophobicity are second only to carbon-fluorine bonds (e.g., CF2 or CF3). This is why polydimethylsiloxane (PDMS) is widely used as a water-repellent surface.
[0005] 2. Depending on weather conditions, curing may stall, resulting in an uncured interior and a cured top surface, thus creating performance differences across the coating width.
[0006] Among compounds with hydrolyzable Si-X groups used in coating formulations, organopolysilazanes (OPSZ) are popular and widely used in coating vehicles to impart stain resistance and UV protection to automotive paints. OPSZ coatings are also applied to solar PV glass, windows, eyeglasses, touchscreens, etc., as stain-resistant or easy-to-clean surfaces.
[0007] The generally recommended curing method for OPSZ is to store and cure in the ambient environment, with curing (up to 95%) requiring up to 7 days. The inventors have noted that OPSZ coatings, whether commercially available or in-house formulated, exhibit very limited or poor curing even after heating at 200°C for 1-2 hours. Therefore, using such high temperatures, which may be infeasible for some substrates (e.g., plastics), does not necessarily lead to satisfactory curing. Even after increasing the relative humidity to over 50%, the inventors found that, as with curing at approximately 900 cm⁻¹… -1 The disappearance of the NH (or Si-NH or Si-NH-Si) FT-IR peak at elevated temperatures demonstrates that curing remains poor or limited at elevated temperatures. Therefore, a cost-effective and time-efficient process is still needed that leads to (near) complete curing of polysilazanes and other compounds containing hydrolyzable Si-X groups.
[0008] Patent application WO2023 / 282768 A1 teaches an improved curing method for polysilazanes, involving the following process: a) drying in an oven maintained at 80°C for 10 min, followed by b) curing in a high-humidity atmosphere containing H2O2 vapor. The authors note that for coating formulations not containing the crosslinking catalyst tetrabutylammonium fluoride (TBAF), curing—the hydrolysis of Si-NH to form silanols and subsequent condensation to produce Si-O-Si—is limited, as is the case with coatings containing TBAF when placed under ambient conditions for curing. Tetrabutylammonium chloride (TBAC) is also known to enhance the curing of polysilazanes. TBAC and TBAF belong to a class known as quaternary ammonium salts (QAS). QAS are readily hydrated, and this may be the reason they are able to enhance the curing of polysilazanes.
[0009] A polysilazane coating method is also described in WO 2022 / 002844 A1. In this method, polysilazane, a catalyst (TBAF), and reactive nanomaterials and / or reactive molecules are introduced into a coating composition container, and the solution is mixed for a predetermined time period. Then, for an additional predetermined time period after the mixing step, the mixed solution is applied to a substrate, and a coating is formed thereon and subsequently cured.
[0010] The object of this invention is to improve the curing method of coatings containing hydrolyzable Si-X groups. A secondary object of this patent is to enhance the curing of polysilazane coating formulations that do not contain QAS, such as TBAF. Summary of the Invention
[0011] This invention provides a method for curing a layer deposited on a substrate, the layer comprising a coating formulation containing hydrolyzable Si-X groups, wherein X is selected from halogens, C 1- C6 alkoxy, hydrogen, -NH-Si, or -NH2, wherein the coating formulation is dissolved in a solvent, the method includes the following steps: a) Heating the layer at a temperature not exceeding 20°C above the solvent's boiling point, and b) Expose the layer to curing vapor.
[0012] Furthermore, the present invention provides a substrate prepared using the method of the present invention. Detailed Implementation
[0013] This invention provides an improved and rapid method for curing a layer deposited on a substrate, wherein the layer comprises a coating formulation containing hydrolyzable Si-X groups, wherein X is selected from halogens, alkoxy groups, hydrogen, NH-Si, and NH2. Examples of compounds containing hydrolyzable Si-X groups include (poly)alkoxysilanes, (poly)halosilanes, and (poly)silazanes. Their hydrolysis and condensation reactions can be summarized as follows: Si-X + H2O=Si-OH + HX……………………(1) Si-OH + Si-OH=Si-O-Si + H2O……………………(2) X can be a halogen, preferably chlorine or bromine (e.g., chlorine in dimethyldichlorosilane), an alkoxy group—e.g., ethoxy in (3-aminopropyl)triethoxysilane (APTES) and a methoxy group—e.g., hydrogen in polysilazanes, and NH-Si or NH2 in polysilazanes. The hydrolysis of Si-NH-Si in polysilazanes has different stoichiometry and results in the formation of two silanol molecules and ammonia: Si-NH-Si + H2O=Si-OH + Si-NH2…………(3) Si-NH2+ H2O=Si-OH + NH3……………………(4) Therefore, the combined equation is: Si-NH-Si + 2H2O= 2Si-OH + NH3……………………(5) Therefore, X in equations 3 and 4 are NH-Si and NH2, respectively.
[0014] Coating formulations comprising hydrolyzable Si-X groups, wherein X is selected from halogens, C1-C6 alkoxy groups, hydrogen, NH-Si, or NH2, and can be dissolved in one or more solvents. The solvent can be a polar aprotic solvent and / or a nonpolar solvent. For Si-X, when X is an alkoxy group, polar solvents such as ethanol or acetone can be used. The solvent can be an anhydrous solvent. In some embodiments, all components are completely dissolved or suspended in a stable suspension before they are introduced into the coating composition container. In other embodiments, one or more liquid components are introduced into the coating composition container in pure form (i.e., without solvent), while all other components are completely dissolved or suspended in a stable suspension before they are introduced into the coating composition container. In some embodiments, all components are dissolved or suspended in the same solvent. In other embodiments, different solvents are used for two or more components. In some embodiments, the solvent is selected from, but is not limited to, the following list: dimethyl sulfoxide (DMSO), n-butyl acetate, tert-butyl acetate, tetrahydrofuran (THF), dimethylformamide (DMF), 2-methyltetrahydrofuran (MTHF), dibutyl ether (DBE), and xylene. In preferred embodiments, coating compositions comprising a large amount of PHPS include only nonpolar solvents such as dibutyl ether and xylene.
[0015] The substrate can be glass, ceramic, metal, polymer (plastic), wood, or composite material. The substrate can be rigid or flexible.
[0016] When the coating formulation is deposited as a layer on the substrate, the layer is heated at a temperature no greater than 20°C above the solvent's boiling point. Preferably, the temperature is no greater than 10°C above the solvent's boiling point. Alternatively, the temperature can be equal to the boiling point. In embodiments of the invention, the layer can be heated at a temperature 10 to 20°C lower than the solvent's boiling point. In one embodiment, where butyl acetate is used as the solvent, the temperature can be 30 to 60°C lower than the solvent's boiling point.
[0017] As mentioned earlier, curing in a humid atmosphere is a surface-to-inside process. This means that curing begins or is faster on the top layer, which is more exposed to moisture. A natural consequence of this is that curing may stall due to the formation of a cured and waterproof layer. Once this cured top layer reaches a sufficient thickness, it will allow for a dry-to-touch state and good surface properties (e.g., a high water contact angle), even without deep curing. However, deep curing is crucial for ensuring the product's durability in demanding applications.
[0018] The heating step can promote more uniform drying through the thickness of the layers. Over-drying or uneven drying means that the top surface is drier than the potentially wetter bottom layer.
[0019] The temperature and duration of the heating step can be preferably controlled so that the coating does not become completely dry.
[0020] Drying means densifying the coating, which involves a more compact packing of polysilazane molecules. This results in greater steric hindrance and greater resistance to curing vapors. The more compact packing of polysilazane molecules may lead to the faster formation of an inert top segment during the early stages of drying and / or curing vapor treatment, which then prevents curing vapors from penetrating the underlying hydrolyzable polar Si-X groups.
[0021] Drying can be carried out over a period of no more than 20 to 30 minutes. Drying can be carried out over a period of 10 seconds to 30 minutes, preferably 20 seconds to 20 minutes, preferably 10 seconds to 10 minutes, preferably 20 seconds to 5 minutes, preferably 20 seconds to 2 minutes, or preferably 30 seconds to 1.5 minutes.
[0022] The curing vapor includes compounds known in the art that hydrolyze or promote the hydrolysis of Si-X groups. The curing vapor may include water, H₂O₂, NH₃, or organic / inorganic acids or combinations of two or more compounds.
[0023] The solidified compound may initially exist as a liquid and therefore must be converted into a gaseous phase. The generation of vapor can be accomplished by any suitable method, such as using heat.
[0024] Steam can be generated using any other known methods known in the art, such as methods for generating water vapor from water—for example, for humidification purposes. Examples include ultrasonic and impeller humidifiers.
[0025] A preferred embodiment uses an ultrasonic humidifier to generate solidified vapor. The ultrasonic humidifier uses ultrasonic frequencies to atomize (vaporize) a liquid into a fine mist, and in this patent document may be referred to as an ultrasonic vaporizer.
[0026] The impeller steam generator uses a high-speed rotating disc (impeller) to break up liquid into fine droplets that can float in the air, and may be referred to as an impeller vaporizer in this patent document.
[0027] The curing vapor may comprise a mixture of water and H2O2. The curing vapor may comprise 1 to 30 wt% H2O2 in water, preferably 5 to 25 wt% H2O2 in water. Preferably, the concentration of H2O2 in water is 10 wt% or higher.
[0028] The curing vapor may include a mixture of ammonia and water. The curing vapor may include 0.25 to 30 wt% NH3 in water, preferably 2 to 20 wt% NH3 in water.
[0029] The percentages of (H2O2 and NH3) in water mentioned above refer to the composition of the liquid that produces the solidification vapor. It is assumed that the produced vapor will have the same concentration as the liquid.
[0030] After the coating has been exposed to curing vapor, it can be heated to complete or further enhance the curing process. Preferably, the temperature is not higher than 200°C for 60 minutes or less.
[0031] In the curing experiments described below, the coating formulation contains polysilazane. The curing method can also be carried out on coating formulations containing hydrolyzable Si-X groups, where X is selected from halogen or alkoxy groups.
[0032] experiment General instructions for the experiment: Unless otherwise stated, the solidification vapor is 20 wt% H2O2 in water.
[0033] For simplicity, % H2O2 vapor refers to vapor produced from an aqueous solution containing the same percentage of H2O2. That is, the H2O2 concentration in the liquid phase and the gas phase are considered to be the same.
[0034] • H2O2 vapor is generated by an ultrasonic humidifier and redirected or uniformly distributed by airflow from the oven fan. The vapor generated by the humidifier is gentle and easily dispersed, so the redirection and distribution of air / gas is crucial for the uniform processing of the sample.
[0035] • Curing vapor is any vapor capable of hydrolyzing the polar groups in polysilazane to form silanols (Si-OH).
[0036] • Curing grades range from 6.75 (almost no curing) to 1 (excellent curing): 1-1.125 (excellent curing, EC); 1.25-1.5 (very, very good curing, VVGC); 1.75-2 (very good curing, VGC); 2.25-2.75 (good curing, GC); 3-3.5 (moderate curing, FC); 3.75 (critical curing, BC); 4-4.5 (poor curing, PC); 4.75-5.5 (very poor curing, VPC); and 5.75-6.75 (extremely poor curing, EPC).
[0037] • Curing grade is based on FT-IR measurement.
[0038] D1500RC is an organopolysilazane containing (3-aminopropyl)triethoxysilane (APTES) to ensure rapid curing. Its structure is believed to be:
[0039] (a, b, and c are proprietary information) 7640 Permanent Protect (PP) is a commercial formulation of organopolysilazane from Creative Chemical Manufacturers, CCM. According to CCM, it contains APTES. Butyl acetate is the main solvent and constitutes 35%–<55% of the composition, while the organopolysilazane constitutes 15%–<35%, and APTES constitutes 5%–<10%.
[0040] The boiling point of n-butyl acetate is 126℃.
[0041] TBAF is a solution of tetrabutylammonium fluoride in THF (0.5 wt%). TBAF acts as a crosslinking catalyst to prevent or minimize fragmentation.
[0042] TG4 is a solution of TEGO® Glide 410 (from Evonik) in THF (5.5 wt%). TG4 is a polyether-modified siloxane and acts as a leveling agent.
[0043] The boiling point of THF is 66℃.
[0044] B17 is a dumbbell-shaped POSS solution (10 wt%) in THF. Its structure is shown below:
[0045] A85 is a solution of open-cage POSS (trisilyl isobutyl POSS, derived from Hybrid Plastics) – 10 wt% in THF. The structure is shown below: R = Isobutyl Coating formulations: ·B17-66: A: 2000 µl D1500RC + 1000 µl TG4 B: 2000 µl B17 POSS + 660 µl TBAF + 250 µl THF ·B17-80 A: 1182 µl D1500RC + 590 µl TG4 B: 1420 µl B17 POSS + 400 µl TBAF + 2318 µl THF ·A85-8 A: 1182 µl D1500RC + 590 µl TG4 B: 1182 µl A85 + 400 µl TBAF + 2550 µl THF ·PP-1: 3940 µl PP + 3940 µl n-butyl acetate ·D1500-R2: 2000 µl D1500RC + 3910 µl THF ·D1500-R9: 2000 µl D1500 RC + 9820 µl n-butyl acetate Experiment 1 • Preparation of coating formulations by combining two solutions (B17-66): A: 2000 µl D1500 RC + 1000 µl TG4 B: 2000 µl B17 POSS + 660 µl TBAF + 250 µl THF The two solutions are mixed by vortexing and allowed to stand for 5 minutes before ultrasonic spraying.
[0046] • Apply the formulation to the glass slide substrate using an ultrasonic sprayer with the following parameters: flow rate 0.8 ml / min, speed 25 mm / s, line spacing 10 mm, air pressure 0.45 bar, height 50 mm, and operating power 36%.
[0047] After drying, the coating is cured by exposing it to H2O2 vapor in an oven maintained at 70°C for 10 minutes, and then heating it in an oven at 120°C for 1 hour.
[0048] The drying conditions and the obtained curing levels are shown in Table 1, and it is shown that for the same drying duration, drying at 55°C results in better curing than at 70°C, while curing at 70°C is better than at 100°C.
[0049] The cured coating has an average thickness of 8.5 µm.
[0050] When drying at 55°C for 30 minutes, the level of curing is approximately the same or similar to that when drying at 100°C for 10 minutes. This indicates that even at lower drying temperatures, shorter drying durations are beneficial for enhanced curing.
[0051] Table 1
[0052] Experiment 2 A coating formulation (A85-8) was prepared by combining two solutions: A: 1182 µl D1500 RC + 590 µl TG4 B: 1182 µl A85 POSS + 400 µl TBAF + 2250 µl THF The two solutions are mixed by vortexing and allowed to stand for 5 minutes before ultrasonic spraying.
[0053] The formulation was applied to the glass slide substrate using an ultrasonic sprayer with the following parameters: flow rate 0.8 ml / min, speed 25 mm / s, line spacing 10 mm, air pressure 0.45 bar, height 50 mm, and operating power 36%.
[0054] After drying, the coating is cured by subjecting it to a high humidity atmosphere containing H2O2 vapor at 70°C for 10 minutes and then heating it in an oven at 120°C for 1 hour.
[0055] The drying conditions and the resulting curing levels are shown in Table 2, and it is shown that drying at 55°C for 2 minutes resulted in better curing than drying at the same temperature for 10 minutes, which in turn resulted in better curing than drying at 100°C for 10 minutes.
[0056] The cured coating has an average thickness of 3.7 µm.
[0057] Table 2
[0058] Experiment 3 Two solutions were prepared: A: 200 µl D1500 RC + 100 µl TG4 + 700 µl THF B: 100 µl A85 POSS + 32 µl TBAF + 868 µl THF Therefore, an ultrasonic sprayer is used to apply the coating formulation to the glass slide substrate: First, spray part B with the following parameters: flow rate 0.4 ml / min, speed 25 mm / s, line spacing 10 mm, air pressure 0.45 bar, height 50 mm, and operating power 36%.
[0059] After 4-5 minutes, spray part A with the same parameters.
[0060] After drying, the coating is cured by subjecting it to a high humidity atmosphere containing H2O2 vapor at 70°C for 10 minutes, and then heating it in an oven at 120°C for 1 hour.
[0061] The average thickness of the cured coating is 2.3-2.5 μm.
[0062] • Samples were dried at 70°C for 30, 60, and 80 seconds. The achieved cure levels were similar, ranging from 1.25 to 1.5. This indicates that rapid exposure to warm air is sufficient to dry the coating for the curing process.
[0063] Experiment 4 • Coating formulation (PP-1): 3940 µl PP + 3940 µl butyl acetate Therefore, the preparation was applied to the glass slide substrate using an ultrasonic sprayer: flow rate 0.8 ml / min, speed 35 mm / s, line spacing 7 mm, air pressure 0.45 bar, height 50 mm, and operating power 36%.
[0064] After drying, the coating is cured by subjecting it to a high humidity atmosphere containing H2O2 vapor at 70°C for 10 minutes, and then heating it in an oven at 120°C for 1 hour.
[0065] • The average thickness of the cured coating is 4-4.5 μm.
[0066] The drying conditions and the obtained curing levels are shown in Table 3, indicating that drying at 60°C for 5 minutes is slightly better than drying at 115°C for 5 minutes, and both are significantly better than drying at 160°C for 5 minutes. Sample 2, dried at 70°C for 1.5 minutes, showed better curing than drying at 60°C for 5 minutes, demonstrating that even with high-boiling-point solvents, low-temperature drying for a short duration of less than 5 minutes is sufficient to prepare coatings for curing.
[0067] Table 3
[0068] Experiment 5 • Coating formulation (PP-1): 3940 µl PP + 3940 µl butyl acetate Therefore, the preparation was applied to the glass slide substrate using an ultrasonic sprayer: flow rate 0.8 ml / min, speed 35 mm / s, line spacing 7 mm, air pressure 0.45 bar, height 50 mm, and operating power 36%.
[0069] After drying, the coating is cured by exposing it to a high-humidity atmosphere containing H2O2 vapor at 70°C for 10 minutes, and then heating it in an oven at 120°C for 1 hour. The concentration of liquid H2O2 in the ultrasonic humidifier varies between 20 and 2.5 wt%.
[0070] • The average thickness of the cured coating is approximately 4.5 μm.
[0071] The drying and curing conditions, as well as the obtained curing levels, are shown in Table 4. The results show that the curing levels achieved range from average to good at concentrations as low as 5% H2O2.
[0072] Table 4
[0073] Experiment 6 • Two coating formulations were prepared: oB17-80 (mix part of A and B by vortexing for 5 minutes) A: 1182 µl D1500 RC + 590 µl TG4 B: 1420 µl B17 POSS + 400 µl TBAF + 2318 µl THF oD1500-R2 2000 µl D1500RC + 3910 µl THF Therefore, an ultrasonic sprayer was used to apply the formulation to the glass slide substrate; the flow rate was 0.3 ml / min, the line spacing was 7 mm, the air pressure was 0.45 bar, the height was 50 mm, and the operating power was 36%. The speeds for B17-80 and D1500-R2 were 50 and 40 mm, respectively. B17-80 was applied in two layers, i.e., sprayed twice, while D1500-R2 was applied in a single layer.
[0074] • After drying at 70°C for 1.5 min, the coating is cured by subjecting it to a high-humidity atmosphere containing H2O2 vapor at 70°C for 1.5 min. Thereafter, the coating is heated for a specific duration.
[0075] • The average thickness of the cured coating is approximately 3 μm.
[0076] The H2O2 post-treatment conditions are listed in Table 5, and it is indicated that: 1) For B17-80, heating at 120°C for 10, 30, and 60 minutes did not provide significant changes in cure level, while for D1500-R2, heating for 30 and 60 minutes at the same temperature showed slightly better cure than heating for 10 minutes. However, the latter gave a good to very good cure level. This suggests that a heating time of 10 minutes or less after H2O2 or heating at a lower temperature is sufficient to achieve good cure.
[0077] 2) In the absence of H2O2 post-heating, the curing levels of B17-80 range from fair to good, while for D1500-R2, the curing levels range from poor to very poor. The presence of TBAF (quaternary ammonium salt (QAS)) in B17-80 improves curing, as previously disclosed in WO2023 / 282768 A1, while its absence in D1500-R2 results in limited curing without additional H2O2 exposure to post-heating.
[0078] Table 5
[0079] As can be seen from the above experiments, the curing method according to the present invention shows that excellent curing of the coating formulation deposited on the substrate as a layer can be obtained at low temperature and within a short curing time.
Claims
1. A method for curing a layer deposited on a substrate, said layer comprising a coating formulation containing hydrolyzable Si-X groups, wherein X is selected from halogens, C 1-6 The coating formulation contains alkoxy, hydrogen, -NH-Si, or -NH2, and is dissolved in a solvent. The method includes the following steps: a) Dry the layer at a temperature not exceeding 20°C above the boiling point of the solvent, and b) Expose the layer to curing vapor.
2. The method according to claim 1, wherein, Steps a) and b) are performed simultaneously.
3. The method according to claim 1 or 2, wherein, The solidification vapor includes one or more of water, H2O2, NH3, organic acids, and inorganic acids.
4. The method according to any one of the preceding claims, wherein, The solidification vapor contains 1 to 30 wt% H2O2 in water.
5. The method according to any one of the preceding claims, wherein, Drying is carried out at a temperature not exceeding 10°C above the boiling point of the solvent.
6. The method according to any one of the preceding claims, wherein, Step a) should be performed within a timeframe of no more than 20 to 30 minutes.
7. The method according to any one of the preceding claims, wherein, Step a) is performed within a time period of 10 seconds to 30 minutes, preferably 30 seconds to 5 minutes.
8. The method according to any one of the preceding claims, wherein, After the layer is subjected to the curing vapor, the layer is heated to a temperature equal to or higher than the boiling point of the solvent.
9. The method according to claim 8, wherein, The temperature is below 200°C for 60 minutes or less.
10. The method according to any one of the preceding claims, wherein, X is selected from chlorine, bromine, methoxy, ethoxy, hydrogen, NH-Si, or NH2.
11. The method according to any one of the preceding claims, wherein, The solvent is selected from tetrahydrofuran (THF), 2-methyltetrahydrofuran (MTHF), n-butyl acetate, tert-butyl acetate, or dibutyl ether (DBE).
12. A substrate manufactured using the method of any one of the preceding claims.
Citation Information
Patent Citations
Polysilazane coating method and device
WO2022002844A1
Polysilazane compositions
WO2023282768A1
